A systematic review of placebo‐controlled trials of topiramate: How useful is a multiple‐indications review for evaluating the adverse events of an antiepileptic drug?. (8th October 2015) - Donegan, Sarah; Dixon, Peter; Hemming, Karla; Tudur‐Smith, Catrin; Marson, Anthony
Summary: Objective: Topiramate (TPM) is an antiepileptic drug that is also used for other indications (e.g., migraine). Adverse event (AE) data from epilepsy trials could be supplemented by data from trials in other indications. Combining data across trials and indications is a novel method for evaluating AEs. We conducted a multiple‐indications review by systematically reviewing randomized placebo‐controlled trials of TPM, to compare the nervous system AEs of TPM in epilepsy with those in other indications. Methods: Randomized placebo‐controlled trials of TPM including patients with any indication were included. We searched Cochrane Central Register of Controlled Trials (Issue 2, 2012) and MEDLINE (1966–February 2012). Two authors assessed eligibility and risk of bias, and extracted data. For each reported nervous system AE, we extracted event rates, applied random‐effects inverse‐variance meta‐analysis (pooling within‐indications then across‐indications), and assessed within‐ and across‐indication heterogeneity. Results: Ninety trials, including 16 epilepsy trials, were included. A difference was detected between TPM and placebo for three events (i.e., drooling, dysgeusia, and hypoesthesia) that were not reported in epilepsy trials but were reported by other trials. A difference between TPM and placebo was detected for speech disorder using epilepsy trials but not when combining all trials. For two events (i.e., cognitive disorder and "language problems"), no difference was detected between TPM and placebo when using epilepsy trials alone, but a difference was identified using all trials. A difference was detected between TPM and placebo for six events (i.e., ataxia, disturbance in attention, dizziness, memory impairment, paraesthesia, and somnolence) when using epilepsy trials alone, and using all trials. Significance: Including trials of any indication enabled detection of differences that would have been missed using epilepsy trials alone. Multiple‐indications reviews can improve the synthesis of AEs for antiepileptic drugs.